STUDENTS PERCEPTIONS ON IMPLEMENTATION OF LEARNING PROCESS IN THE DEPARTMENT OF CIVIL ENGINEERING STATE UNIVERSITY OF PADANG ON SEMESTER JANUARY-JUNE 2014 - 521-528 , M. Abdullah (CIVED, 2015)
Abstract   This research  was motivated  by the fact  that there  are many  students who repeat courses in semester January-June and not seriously to present the learning process. This is a descriptive  research  which  aims to  reveal  students'  perceptions on  the  implementation  of learning process in the Department of Civil Engineering, State University of Padang, in semester January-June 2014. The population was all students of S1 and D3 actively taking courses in the Department of Civil Engineering in semester January–June 2014. Samples were taken purposively by using Slovin formula with 82 students samples of S1 and 76 students samples  of D3. The research data were obtained from questionnaires that given to students, and then analyzed with percentage technique. The results showed that D3 students' perceptions on the learning process in term of student assessment on the lecture material are  very good, students assessment on the lecturer is very good, student assessment on  the presentation of the material is good, and student discipline classroom assessment is good. S1 students' perceptions on the learning process in terms of student assessmenton the lecture material is very good, students assessment on the lecturer is very good, student assessment on the presentation of the material is good, and student discipline classroom assessment is good. This research recommended  for  lectures  to  work  more  variance  and  interesting  on  learning  process  to students , that makes students have more spirits to present the learning process because a little bit bad perceptions from students should be get respons from lectures in Department Of Civil Engineering subject.   Keywords: Perceptions, Learning process, The Department of  Civil Engineering